SOCIO-ECOLOGICAL ANALYSIS OF AGRICULTURAL ACTIVITIES IN THE BUFFER AREA OF THE NANTU BOLIOHUTO WILDLIFE SANCTUARY, GORONTALO - Widodo, Eka Reza Saputra; Rauf, Asda; Hamidun, Marini Susanti (Universitas Gorontalo, 2026)
This study analyzes the socio-ecological dynamics of land management in Sari Tani Village, located within the buffer zone of the Nantu Boliohuto Wildlife Sanctuary (SM). Previous studies have focused more on the biophysical aspects of land degradation and the impacts of agricultural activities on conservation areas, but have been limited in integrating the analysis of inter-factor relationships, land management strategies by different social groups, and the role of local institutions within a comprehensive socio-ecological framework. The study was conducted over two months using a qualitative approach through field observations and in-depth interviews with 40 farmers (20 local and 20 transmigrants), village officials, middlemen, community leaders, agricultural extension workers, and forestry agencies. Data were analyzed using a Social-Ecological System (SES) framework to capture the interrelationships between resource systems, resource units, actors, and governance. The results indicate that the degradation of resource systems and resource units is influenced by differences in management strategies between local and transmigrant farmers. Local farmers tend to open new land due to monoculture practices that reduce soil fertility, while transmigrant farmers adopt a relatively more adaptive and conservative intercropping pattern. Weak governance, minimal institutional coordination, and the dominant role of middlemen contribute to reinforcing incentives for land expansion. Interactions between actors demonstrate that land-use decisions are driven more by short-term economic motives than by ecological sustainability considerations. This research emphasizes the importance of strengthening collaborative governance, implementing conservation agriculture practices, and integrating local knowledge into buffer zone management. These findings are expected to fill the research gap related to socio-ecological analysis in conservation areas and serve as a reference for policy formulation and the development of sustainable landscape management models in protected area buffer zones.